Multisensory Design: Reaching Out to Touch the Consumer - Spence, C; Gallace, A (2011)
Touch plays an important, if often underacknowledged, role in our evaluation/appreciation of many different products. It is unsurprising, therefore, that there has been such a recent growth of interest in "tactile branding" and tactile marketing. This article reviews the evidence from the fields of marketing, psychology, and cognitive neuroscience, demonstrating just how important the feel of a product, not to mention the feel of its packaging, can be in determining people's overall product evaluation. Problems for tactile design associated with the growth of the aging population, and the growth of Internet-based shopping, are highlighted. The critical role that touch can play in multisensory product design, appreciation, and marketing is also discussed, as is the increasingly frequent use by marketers of synesthetic correspondences to evoke tactile sensations via the visual and auditory modalities. We put forward the argument that tactile stimulation may influence multisensory product evaluation by means of affective ventriloquism: Our suggestion is that the hedonic attributes of a product perceived via one modality (such as touch) can "pull" (or bias) a person's estimates of the quality and pleasantness of the product derived from other sensory modalities into alignment, and by so doing, modulate a person's overall (multisensory) product experience. What is more, powerful mathematical modeling approaches now exist to predict the magnitude of this kind of intersensory (or crossmodal) interaction effect, hence offering the promise of a more scientific approach to tactile design/marketing in the coming years. © 2011 Wiley Periodicals, Inc.